2007
DOI: 10.2139/ssrn.1107509
|View full text |Cite
|
Sign up to set email alerts
|

Protection of Property Rights and Growth as Political Equilibria

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 88 publications
1
18
0
1
Order By: Relevance
“…Successive literature reviews by Armey (1995), Abdiweli (2003) and Asoni (2008) have confirmed the consensus that institutions matter for growth. In addition to the importance of well‐defined property rights, Abdiweli empirically confirmed that judicial efficiency, low levels of corruption and a well‐organized public bureaucracy also co‐vary positively with high levels of growth.…”
Section: Theoretical Considerationsmentioning
confidence: 88%
“…Successive literature reviews by Armey (1995), Abdiweli (2003) and Asoni (2008) have confirmed the consensus that institutions matter for growth. In addition to the importance of well‐defined property rights, Abdiweli empirically confirmed that judicial efficiency, low levels of corruption and a well‐organized public bureaucracy also co‐vary positively with high levels of growth.…”
Section: Theoretical Considerationsmentioning
confidence: 88%
“…To dig deeper, there are specific types of institutions under these headings which also could be expected to have a greater influence on financial markets. As the sine qua non of economic institutions, property rights have been proven empirically to be a foundation for transition dynamics (Hartwell 2013), economic growth (Torstensson 1994, Acemoglu and Johnson 2005, Asoni 2008, and many others), and, most importantly for our purposes, the development of an effective financial sector (Clague et al 1999, Andrianaivo andYartey 2009).…”
Section: Stock Markets and Institutionsmentioning
confidence: 99%
“…According to North (1992), good institutions facilitate low transaction costs which in turn galvanize economic growth. In the context of formal institutions, property rights hold a principal position among all economic institutions which is in line with extensive research on its impact on economic growth (see for instance, Acemoglu et al, 2001;Asoni, 2008;Besley and Ghatak, 2009;Kerekes and Williamson, 2008). The rule of law's impact on economic growth can be summarised in three areas as described by Haggard et al (2008).…”
Section: Institutions and Economic Growth: Theoretical Considerationsmentioning
confidence: 67%